2013
DOI: 10.1071/fp13191
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics to study stress responses in crop legumes: progress and prospects

Abstract: Abstract. Legumes are important food crops worldwide, contributing to more than 33% of human dietary protein. The production of crop legumes is frequently impacted by abiotic and biotic stresses. It is therefore important to identify genes conferring resistance to biotic stresses and tolerance to abiotic stresses that can be used to both understand molecular mechanisms of plant response to the environment and to accelerate crop improvement. Recent advances in genomics offer a range of approaches such as the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 115 publications
0
26
0
3
Order By: Relevance
“…The use of SuperSAGE technique in plant has been widely implemented for studying responses of genes under various biotic and abiotic stresses across different species, such as banana, tobacco, capsicum, chickpea, etc. Utilization of this technique for elucidating role of genes in abiotic stress response has helped in the elucidation of 3,000 stress-related transcripts from 360,000 transcripts of salt-and drought-related transcriptome of chickpea and lentil (Kudapa et al 2013 ). The amenability of SuperSAGE with integrative transcriptome, SuperSAGE microarray, and next-generation sequencing has also led to an increase in its effi ciency towards gene expression profi ling (Matsumura et al 2005 ).…”
Section: Hybridization-based Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…The use of SuperSAGE technique in plant has been widely implemented for studying responses of genes under various biotic and abiotic stresses across different species, such as banana, tobacco, capsicum, chickpea, etc. Utilization of this technique for elucidating role of genes in abiotic stress response has helped in the elucidation of 3,000 stress-related transcripts from 360,000 transcripts of salt-and drought-related transcriptome of chickpea and lentil (Kudapa et al 2013 ). The amenability of SuperSAGE with integrative transcriptome, SuperSAGE microarray, and next-generation sequencing has also led to an increase in its effi ciency towards gene expression profi ling (Matsumura et al 2005 ).…”
Section: Hybridization-based Methodsmentioning
confidence: 97%
“…In legumes, high-density cDNA-based arrays have been employed to study 27,513 unigene sets from various developmental stages and stress-exposed tissues of soybean. The result thus obtained identifi ed a large number of genes involved during different biotic (herbicide and pathogen) and abiotic stresses (drought, heat, fl ooding) (Vodkin et al 2004 ) reviewed by Kudapa et al ( 2013 ). Other legumes such as chickpea have also been subjected to global gene expression analysis by various researchers, and in the year 2010 Mantri et al ( 2010 ) identifi ed differentially expressed genes in varying genotypes, in response to various abiotic stresses by comparing a 768 feature microarray of chickpea cDNA (559), grass pea cDNA (156), lentil resistance gene analogue cDNA (41), and control (12).…”
Section: Hybridization-based Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, gene discovery has been very limited in chickpea. Hence, only a few candidate genes have been cloned and functionally validated (Kaur et al 2008;Shukla et al 2009;Tripathi et al 2009;Peng et al 2010;Kudapa et al 2013). By studying two chickpea varieties (PUSABGD 72 and ICCV 2) for differences in transcript profiling during drought stress treatment by withdrawal of irrigation at different time points, Jain and Chattopadhyay (2010) reported that most of the highly expressed ESTs in the tolerant cultivar predicted that most of them encoded proteins involved in cellular organisation, protein metabolism, signal transduction and transcription.…”
Section: Transcriptome Sequencing In Chickpeamentioning
confidence: 99%